2022
DOI: 10.3390/healthcare10071200
|View full text |Cite
|
Sign up to set email alerts
|

Readiness of Mozambique Health Facilities to Address Undernutrition and Diarrhea in Children under Five: Indicators from 2018 and 2021 Survey Data

Abstract: The World Health Organization’s systems framework shows that service delivery is key to addressing pressing health needs. Inadequate healthcare and the lack of healthcare services are factors associated with undernutrition and diarrhea in children under five, two health conditions with high morbi-mortality rates in Mozambique. The aim of the analysis was to determine the readiness score of nutrition and diarrhea services for children under five and the influence of malaria and HIV (Human Immunodeficiency Virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
2
2
Order By: Relevance
“…Compared to a study in Mozambique, where 58.2% of health professionals received nutrition-related training [34], our study showed a more pronounced emphasis on staff training. This can potentially be attributed to the recent waves of training in the new national guidelines for managing acute malnutrition in Ethiopia [21].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Compared to a study in Mozambique, where 58.2% of health professionals received nutrition-related training [34], our study showed a more pronounced emphasis on staff training. This can potentially be attributed to the recent waves of training in the new national guidelines for managing acute malnutrition in Ethiopia [21].…”
Section: Discussioncontrasting
confidence: 99%
“…The presence of quick reference guides in 73.6% of the facilities and trained staff in 88.9% of them underscores the concerted efforts put forth to bolster the knowledge base and training in these facilities. Compared to a study in Mozambique, where 58.2% of health professionals received nutrition-related training[34], our study showed a more pronounced emphasis on staff training. This can potentially be attributed to the recent waves of training in the new national guidelines for managing acute malnutrition in Ethiopia[21].…”
Section: Discussioncontrasting
confidence: 91%
“…This is similar to a study in Mozambique which showed the percentage of health professionals who received at least one training on nutritional services in the last two years were 58.2%, with training on the feeding of babies and young children being the most reported (40.3%). The study also showed only 33.3% of nutritionists had received training in two years (Sambo et al, 2022).…”
Section: Resultsmentioning
confidence: 88%
“…Similar to other studies on nutrition in Mozambique, our results demonstrate that there are gaps in the Mozambican health system related to the availability and provision of items at health facilities required for adequate delivery of maternal and child nutrition interventions. [37][38][39] We also found that many health facilities offer maternal and child nutri- • Population with access to a health facility-refers to the population that lives within 10 kilometers of any health facility that is ready to deliver nutrition services.…”
Section: Discussionmentioning
confidence: 99%